Implementation of The Al'ab Mudawwar To Improve Memorization of Vocabulary - Shiddiq, Muhammad Danial; Wijaya, Muallim (STUDI ARAB, 2025)
This study aims to describe and measure the effectiveness of the Rotating Games technique in improving students’ Arabic vocabulary retention at the “Excellent Language” dormitory, Zaid bin Thabit boys’ area, Nurul Jadid Islamic Institute, during the first semester of the 2025–2026 academic year. The research employed a mixed methods approach, integrating qualitative and quantitative methods within a case study framework to obtain a comprehensive understanding of the game’s impact on vocabulary learning. A sequential exploratory design was applied, beginning with qualitative data collection through observation and interviews to examine the implementation process, students’ responses, and lecturers’ perspectives. This stage was followed by quantitative data collection using pre-tests and post-tests to measure vocabulary retention objectively. The research sample consisted of 10 students from one class who participated in both tests. The results indicated a significant improvement in students’ vocabulary retention after the implementation of the Rotating Games. Quantitative analysis using descriptive statistics and a paired sample t-test with SPSS revealed statistically significant differences between pre-test and post-test scores in favor of the post-test. Qualitative findings supported these results, showing increased learning motivation, more active participation, and greater confidence in using vocabulary during language interaction. The study concludes that the Rotating Games technique is an interactive and effective strategy for enhancing Arabic vocabulary retention and creating a motivating learning environment, particularly in Islamic educational institutions.